Two-Year Visual Outcomes of Evolution Implantable Collamer Lens and Small Incision Lenticule Extraction for the Correction of Low Myopia - Fu, Mengjun; Li, Meiyan; Xian, Yiyong; Yu, Zhiqiang; Zhang, Haorun; Choi, Joanne; Niu, Lingling; Wang, Xiaoying; Zhou, Xingtao (Frontiers in Medicine, 2022)
Purpose To investigate the 2-year visual quality of Evolution Implantable Collamer Lens (EVO-ICL) and small incision lenticule extraction (SMILE) for the correction of low myopia. Methods In this prospective study, we included 25 eyes of 25 patients (7 men) who underwent EVO-ICL and 36 eyes of 36 patients (16 men) who underwent SMILE between January 2018 and December 2018. Subjective and objective visual outcomes were compared between ICL and SMILE. All patients were followed for 2 years. Results At the postoperative 2-year visit, the percentage of patients with uncorrected distance visual acuity (UDVA) greater than or equal to preoperative corrected distance visual acuity (CDVA) was comparable in the ICL group (80%, 20/25) and SMILE group (88.89%, 32/36). Spherical equivalent (SE) was within ± 0.50 D in 96% (24/25) of the ICL group and 94.44% (34/36) of the SMILE group. No eyes lost more than 2 lines of CDVA. Postoperative high-order aberrations (HOAs) were significantly increased in the ICL group (p < 0.01) and in the SMILE group (p < 0.01). The most common visual complaint was halo after ICL and starburst after SMILE. There was no correlation between HOAs and visual complaints (p > 0.05). Conclusion Evolution Implantable Collamer Lens provides comparable safety, efficacy, long-term visual stability, and high patient satisfaction when compared to SMILE in correcting low myopia. EVO-ICL could be a favorable alternative for low myopia. Key messages What was known? • Visual outcomes of Evolution Implantable Collamer Lens (EVO-ICL) versus small incision lenticule extraction (SMILE) for correction of mild myopia remain unclear. What this paper adds? • Evolution Implantable Collamer Lens (EVO-ICL) provides comparable safety, efficacy, long-term visual stability, and high patient satisfaction when compared to small incision lenticule extraction (SMILE) in correcting low myopia. • The most common visual complaint was halo after ICL and starburst after SMILE.